(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
Freedom of scientific research and drug testing need to be constantly balanced with other interests and fundamental rights. In this field, it is also important to ensure transparency of clinical trials and data. Unfortunately there are many lack of rules that undermine this. Regulation (EU) no. 536/2014 and EMA policy 0070, can contribute to a stepwise action towards reliable and robust data.